2013
DOI: 10.1007/s10071-013-0680-5
|View full text |Cite
|
Sign up to set email alerts
|

Male vocal competition is dynamic and strongly affected by social contexts in music frogs

Abstract: Male-male vocal competition in anuran species is critical for mating success; however, it is also highly time-consuming, energetically demanding and likely to increase predation risks. Thus, we hypothesized that changes in the social context would cause male vocal competition to change in real time in order to minimize the costs and maximize the benefits of competition. To test this hypothesis, we assessed the effect of repeating playbacks of either white noise (WN) or male advertisement calls on male call pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 63 publications
4
36
0
Order By: Relevance
“…Since both male signaling and female choice are dynamic processes in anurans [33,34], acoustic signal processing could be reflected by the dynamic properties of the EEG recorded from the well-organized auditory mesencephalon rather than from the more dispersed neural networks of the auditory telencephalon. Therefore, the fact that the dynamic changes within specific EEG bands over time presented solely in the left mesencephalon but not on either side of the telencephalon probably reflect the existence of structural asymmetries in the auditory midbrain which play a key role in anuran vocal communication and bring about the REA observed in this species.…”
Section: The Key Importance Of the Auditory Midbrain In Anuran Vocal mentioning
confidence: 99%
See 1 more Smart Citation
“…Since both male signaling and female choice are dynamic processes in anurans [33,34], acoustic signal processing could be reflected by the dynamic properties of the EEG recorded from the well-organized auditory mesencephalon rather than from the more dispersed neural networks of the auditory telencephalon. Therefore, the fact that the dynamic changes within specific EEG bands over time presented solely in the left mesencephalon but not on either side of the telencephalon probably reflect the existence of structural asymmetries in the auditory midbrain which play a key role in anuran vocal communication and bring about the REA observed in this species.…”
Section: The Key Importance Of the Auditory Midbrain In Anuran Vocal mentioning
confidence: 99%
“…Thus, a left-hemisphere/right-ear processing advantage for communication sounds in anurans may be mediated by brainstem pathways providing a preferred channel derived from the right ear to the left midbrain and telencephalon. Since both male signaling and female choice are dynamic processes in anurans [33,34], unfolding in real time, REA and its underlying mechanisms would also be expected to estimate by varying dynamically correlated EEG activity in the left hemisphere, especially in the auditory midbrain which is closely associated with the ascending auditory input.…”
Section: Introductionmentioning
confidence: 99%
“…injections of gonadotropin-releasing hormone (gnrH-A6; Sichuan, China; 1.25 μg per animal). After 24 h, the reproductive status of females was determined based on phonotaxis behavior (i.e., approaching a speaker broadcasting male advertisement calls) and that of males was determined by recording call activity as described previously (Cui et al 2011b;Fang et al 2012bFang et al , 2013. Accordingly, neurophysiological and behavioral recordings began 24 h after the hormone injections, and continued for 24 h, mindful of the fact that the induced reproductive behaviors could continue for 3 days or more.…”
Section: Animalsmentioning
confidence: 99%
“…Babina males produce advertisement calls from within hidden burrows whose resonant properties alter the acoustic properties of the calls Cui et al, 2012Cui et al, , 2010. Phonotaxis experiments have shown that 70% of female Babina prefer calls produced from within the burrows, which are hence more highly sexually attractive (HSA) than those produced from outside the burrows, which are less sexually attractive (LSA) and the male Babina prefer competing vocally with HSA calls rather than with LSA calls (Fang et al, 2014a). Electrophysiological studies show that relative power in the alpha, delta and beta bands declines or increases with time in the left but not right mesencephalon, with the most notable changes occurring during playbacks of HSA calls (Fang et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the population level rather than the individual level of lateralization was measured in the present study. As previous EEG studies have shown that conspecific calls most strongly activate the left hemisphere of animals with REA, we predicted that music frogs would turn generally rightwards in order to improve discrimination when hearing conspecific calls, with a stronger preference for HSA than LSA calls Fang et al, 2014a). For other acoustic stimuli, we also predicted that (1) stimuli novel to frogs such as white noise (WN) would elicit either no turning or no orientation preference, and stimuli related to (2) explosive environmental sounds such as thunder or (3) sounds associated with predation would evoke either left turn movement or little preference, as reported in dogs (Reinholz-Trojan et al, 2012;Siniscalchi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%